1997
DOI: 10.1080/02841859709172414
|View full text |Cite
|
Sign up to set email alerts
|

Craniocaudal motion velocity in the cervical spinal cord in degenerative disease as shown by MR imaging

Abstract: The cord showed a higher motion velocity at the compression level than at noncompression levels. This paradoxical increase in velocity was observed in 7 out of 8 patients whose lower extremity motor function was impaired. Four patients with normal lower extremity motor function did not demonstrate this increase in velocity. An increase in motion velocity was therefore found to correlate with impaired lower extremity motor function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 7 publications
2
30
0
Order By: Relevance
“…Several reasons have been proposed for the observed errors including acceleration artefacts and phase contributions 11 , flow related eddy current effects 12,13 , maxwell gradient effects 14 , voxel size related partial-volume effects 15 , relaxation effects 16 , phase errors during the time between velocity encoding and echo, intravoxel velocity distribution 17 and other non-identified effects 13 . Standardized correction for phase drift is needed as it varies between scanners and different timepoints of measurement 10 and was proposed in diverse ways (phantom measurements 2,5,18 , measurements of static tissue 18 ). However, no standardized measurement of spinal cord motion is established yet.…”
Section: Introductionmentioning
confidence: 99%
“…Several reasons have been proposed for the observed errors including acceleration artefacts and phase contributions 11 , flow related eddy current effects 12,13 , maxwell gradient effects 14 , voxel size related partial-volume effects 15 , relaxation effects 16 , phase errors during the time between velocity encoding and echo, intravoxel velocity distribution 17 and other non-identified effects 13 . Standardized correction for phase drift is needed as it varies between scanners and different timepoints of measurement 10 and was proposed in diverse ways (phantom measurements 2,5,18 , measurements of static tissue 18 ). However, no standardized measurement of spinal cord motion is established yet.…”
Section: Introductionmentioning
confidence: 99%
“…This extrapolation, while plausible as a rough estimate, certainly merits additional examination.) These measurements by Tanaka et al (9) appear to lend support to the idea that craniocaudal motion contributes at least in part to signal loss in the cord. Two other arguments may support this notion.…”
Section: Discussionmentioning
confidence: 57%
“…Phase imaging studies of spinal cord velocities have tended to report differences in peak velocities rather than the simultaneous velocity differences needed to compute velocity gradients. Tanaka et al (9), however, reported simultaneous C5/6 to C7/T1 velocity differences equivalent to about .1 (mm/s) mm –1 in a normal volunteer and .9 (mm/s) mm –1 in a patient with C5/6 cord compression, in measurements between 100 ms and 150 ms post R‐wave. (We calculated these velocity gradients by assuming a distance of about 30 mm between the C5/6 and C7/T1 levels, and then extrapolating larger‐scale velocity gradients to estimate the millimeter‐scale intravoxel velocity gradients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations